Annual Assessment of Al-Furat Al-Awsat Technical University ATU Sustainability Development Goals for GreenMetric World University Rankings - Mudhaffar S. Al-Zuhair; Essam O. Al-Zaini; Ahmed Ghanim Wadday (Universitas Diponegoro, 2021)
Al-Furat Al-Awsat Technical university ATU, is one of the newly established academic institutions in Republic of Iraq. Since its emergence in 2014, presently the university is keen to secure its position among other internationally to be a well recognized academic institutions, thereby addressing all sustainable goals and related challenges in its futuristic development schemes. These include developing all existing educational programs and schemes, developing in campus faculty infrastructures, implementing alternative energy resources, developing waste managements, enhancing potable water conservation existing projects and evolving existing transportation structures. This current manuscript highlights in depth all the above indicated developments schemes thereby examining their implementation stages and addressing all associated challenges that face the university. It also looks at its potentials and capabilities to overcome such issues.